Analisis Kepekaan Lingkungan Dan Kebutuhan Bahan Ajar Perubahan Lingkungan Siswa Sman 5 Kota Depok - Deden Ibnu; Sisean Baga; Hafid Abbas; Nadiroh; I Made Astra (Universitas Negeri Jakarta, 2023)
Environmental problems are a necessity that is difficult to separate from human life as a result of human behavior that pollutes the environment. As living beings, humans always try to make ends meet by utilizing natural resources provided by the surrounding environment. The purpose of this study was to determine the level of environmental sensitivity of high school students in Depok City and the need for teaching materials currently used in schools in biology lessons. Research Methods with a survey approach to 90 high school students in Depok City. The results of this study are high school students in Depok's environmental sensitivity is still low and biology learning currently still uses conventional teaching materials and is still relevant to the applicable curriculum. However, what is currently being noted is that teachers are faced with the development of information technology which makes teachers have to adapt and need teaching materials that are adaptive to current technological developments so that learning outcomes can be effective and efficient